Rotativa el Ricaurte (2020)
Rotativa del Ricuarte is a project that has its bases in what this neighborhood is for the city of Bogotá. El Ricaurte neighborhood represents for most Colombians a space of innovation, a milestone for the city and its people, a benchmark of what specialized work in graphic arts is and can come to represent. Currently, the people who work there face daily challenges related to the difficulties that arise from not having spaces created specifically for the industry. Added to all this, the general lack of public spaces that encourage relations between the inhabitants, workers and visitors of the sector, is an opportunity for development and encounter that is being missed. As a result of all this, the question that guided this research was: How to enhance the dynamics of El Ricaurte, taking advertising strategies and trades as an opportunity to explore public space and architecture? It was from this concept that this new urban...